A molecular tweezer antagonizes seminal amyloids and HIV infection - Lump, Edina; Castellano, Laura M; Meier, Christoph; Seeliger, Janine; Erwin, Nelli; Sperlich, Benjamin; Stürzel, Christina M; Usmani, Shariq; Hammond, Rebecca M; von Einem, Jens; Gerold, Gisa; Kreppel, Florian; et al. (eLife, 2015)
Semen is the main vector for HIV transmission and contains amyloid fibrils that enhance viral infection. Available microbicides that target viral components have proven largely ineffective in preventing sexual virus transmission. In this study, we establish that CLR01, a ‘molecular tweezer’ specific for lysine and arginine residues, inhibits the formation of infectivity-enhancing seminal amyloids and remodels preformed fibrils. Moreover, CLR01 abrogates semen-mediated enhancement of viral infection by preventing the formation of virion–amyloid complexes and by directly disrupting the membrane integrity of HIV and other enveloped viruses. We establish that CLR01 acts by binding to the target lysine and arginine residues rather than by a non-specific, colloidal mechanism. CLR01 counteracts both host factors that may be important for HIV transmission and the pathogen itself. These combined anti-amyloid and antiviral activities make CLR01 a promising topical microbicide for blocking infection by HIV and other sexually transmitted viruses.
Keywords: HIV; amyloid; molecular tweezer